(untitled) (Development Service Industry Management, 2023)
Demand in the market of tourist services means the desire and willingness of individuals or groups to purchase various services related to travel, tourism and hospitality. This demand is influenced by a variety of factors, and understanding these factors is important for businesses and destinations in the tourism industry. It should be noted that due to the active influence of globalization processes on the international market of tourist services, corresponding changes are taking place in all national tourist markets. In particular, starting in 2020, business representatives of the tourism and hospitality industry for the first time in history felt a negative impact on the development of the industry as a result of the global pandemic (COVID-2019), the result of which was the introduction at the national level of restrictions on the possibilities of movement of citizens both within states and between them. The purpose of the study is the systematization and analysis of factors motivating tourist trips in Ukraine with the beginning of the military aggression of the Russian Federation. As a result of the influence of internal and external factors in the international and domestic space, the role of the tourism industry in Ukraine underwent significant changes during 2020-2023. Despite the gradual recovery of the industry in 2021 due to the effects of the COVID-19 pandemic, the military aggression of the Russian Federation led to an almost complete stop functioning of tourism business entities. However, 2023 showed certain positive trends in the recovery of the tourism industry, especially in the western regions of Ukraine (Zakarpattia region, Lviv region, Ivano-Frankivsk region), where a significant increase in travelers could be observed. This became one of the factors of the recovery and development of domestic tourism, which, subject to the development of appropriate state regulatory instruments, can become one of the priority areas of economic recovery of Ukraine. When researching current types of recreation in Ukraine, the majority of respondents (54.0%) noted that they prefer hiking and exploring the urban environment. About 28% of respondents prefer cultural tourism (excursions to historical monuments and museums). About 23% of travelers preferred beach tourism. Here it should be noted a significant change in priorities during this period, because according to the results of the survey "Study of domestic and outbound tourism of Ukrainians" conducted by the Human Research company on the order of the State Tourism Development Agency in 2021, the priority type of tourism was precisely beach tourism (about 48% ). Tourism businesses and destinations constantly monitor and adapt to these factors in order to effectively respond to changes in demand and maintain a competitive advantage in the tourism market. Understanding the diverse and changing nature of demand is key to the success of businesses and destinations in the tourism industry. The development of tourism can become a driver of regional development, helping to boost the economy of less developed regions.